Technical training for the use of project-based teaching - Jurča, Robert; Petrucha, Jindřich; Napthine, Andrew (R&E-SOURCE, 2015)
We have been working as teaching staff for years and we can responsibly say that many of the present students lack the technical or logical thinking. That is why we are convinced that even in the area of general subject we can support technical education, through appropriate tools. Why do we think so? We are convinced that present modern days are full of technical resources. That is why we can use these technical resources even in teaching of “non-technical” subjects and to use their function to introduce these technical resources to the students. We are facing the situation where society is developing quickly and it is transforming from the modern society supported by information and communication resources towards searching for the spiritual dimensions and the essence of its being. One of the many conveniences of today is the possibility to implement modern information technologies into teaching. Students will learn not only handle these technologies, but also to use them. There are very convenient elements that interconnect general education and technical education – project learning or problem learning.